2004
DOI: 10.1021/jp036799t
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral and Integral Binding of Cytochrome c to Phospholipids Vesicles

Abstract: The interactions of ferric cytochrome c (Cyt-c) with dioleoyl-phosphatidylglycerol (DOPG) at low ionic strength have been studied by viscosity and turbidity measurements as well as by resonance Raman, circular dichroism, and UV-vis-absorption spectroscopy to monitor the structural changes of the liposomes and the protein upon complex formation. The observed mutual structural changes in the liposomes and the protein are associated with three different modes of protein binding. At high lipid/protein (L/P) ratios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
162
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(181 citation statements)
references
References 38 publications
(75 reference statements)
15
162
2
2
Order By: Relevance
“…The upshift is particularly evident for the (yeast cyt c-CL) complex (Panel B right, trace c), where a RR band due to a five coordinated high spin is also observed at 1495 cm −1 [6]. Similar changes have been previously observed also upon binding of ferric horse cyt-c to anionic dioleoyl-phosphatidylglycerol (DOPG) vesicles [29]. The pronounced saddle-distortion [30] of the heme group in native cyt c is responsible of the lower core size marker bands frequencies in the RR spectrum compared to planar heme proteins, which display an inverse correlation between RR band frequencies and the porphyrin core size [31][32][33].…”
Section: The (Cyt C-cl Liposome) Interactionsupporting
confidence: 75%
“…The upshift is particularly evident for the (yeast cyt c-CL) complex (Panel B right, trace c), where a RR band due to a five coordinated high spin is also observed at 1495 cm −1 [6]. Similar changes have been previously observed also upon binding of ferric horse cyt-c to anionic dioleoyl-phosphatidylglycerol (DOPG) vesicles [29]. The pronounced saddle-distortion [30] of the heme group in native cyt c is responsible of the lower core size marker bands frequencies in the RR spectrum compared to planar heme proteins, which display an inverse correlation between RR band frequencies and the porphyrin core size [31][32][33].…”
Section: The (Cyt C-cl Liposome) Interactionsupporting
confidence: 75%
“…It appears that the mode of cyt c-lipid binding and the possibility of insertion depend on the lipid composition and surface coverage (9,41). Estimates of the heme location with dye-labeled CL in the similar TOCL/ DOPC lipid vesicles have placed the heme within 9-17 Å from the center of the bilayer (42).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the main low-spin bis-His heme species (heme is coordinated by His18 and His26 or His33), resonance Raman studies have found subpopulations of high-spin five-and six-coordinate hemes (9). Several cyt c-CL interaction models have been proposed.…”
mentioning
confidence: 99%
“…Furthermore, as Lys79 is the amino acid assumed to replace Met80 as the axial ligand of the heme iron at alkaline pH, we envisage that a similar event may take place during formation of the cyt c−CL complex at neutral pH. 8,31,41,42 The unfolding of the region of residues 60−92 induced by the insertion of the acyl chain destabilizes the native Met80−Fe(III) axial bond and facilitates the replacement of the Met80 residue as the axial ligand by another residue, identified by RR measurements as Lys79. These results in part rectify the extended cardiolipin anchorage to cyt c model, which proposed Lys72 and Lys73 as the residues involved in the molecular recognition with CL; 7 on the other hand, they are in agreement with our model asserting that the CL phosphate groups interact with the protein in the vicinity of the Lys72 and Lys79 amino groups.…”
Section: ■ Discussionmentioning
confidence: 99%